Polish society towards the implementation of the circular economy and the change of municipal waste management - ecological, economic and social aspekt = Polskie społeczeństwo wobec wdrażania gospodarki o obiegu zamkniętym i zmianie gospodarki odpadami komunalnymi - aspekt ekologiczny, ekonomiczny i społeczny - Zarębska, Joanna; Zarębski, Andrzej; Lewandowska, Anna (Zielona Góra: Faculty of Economics and Management Press)
Circular economy (CE) is seen as a key strategy for achieving sustainable development (SD). One of the components of SD is sustainable production and consumption. Poland, as an EU member state, has for many years been trying to imitate the good practices of other countries in the field of sustainable production and consumption, and above all, in reducing the amount of waste generated. However, the country`s economic situation, pandemic, people`s mentality, habits and other ecological, economic and social factors mean that the pursuit of CE is very slow.
Keywords: circular economy; waste management; concern for the environment; development barriers; gospodarka o obiegu zamkniętym; gospodarowanie odpadami; troska o środowisko; bariery rozwojowe